Effects of Various Chairside Surface Treatments on Zirconia-Resin Cement Bond Strength - Elif Yeğin (Journal of Dental Materials and Techniques, 2019)
Introduction: Various surface treatments have been used to improve the adhesion of resin cement to zirconia restorations. The present study aimed to investigate the effects of different surface treatments on the bond strength of resin cement to zirconia (Y-TZP) in clinical practice. Methods: thirty square Y-TZP samples were classified into three groups of 10, including group SB (50 µm sandblasted Al2O3 particles), group B (diamond burs), and group C (control). One sample from each group was subjected to X-ray powder diffraction, scanning electron microscopy (SEM), and profilometer analysis. The shear bond strength (SBS) of zirconia-resin cement was measured using a universal testing machine at the crosshead speed of 1 mm/min until bonding failure. SBS values were analyzed using analysis of variance (ANOVA) and Tukey’s HSD test (α=0.05). Results: According to the results of ANOVA, SBS was significantly affected by the treatment method. Tukey’s HSD test showed significant differences between the groups (P